Metagenomic analysis of gut microbial communities from a Central Asian population - Bork, Peer; Letunic, Ivica; Sunagawa, Shinichi; Kandels-Lewis, Stefanie; Benes, Vladimir; Voigt, Anita Yvonne; Hercog, Rajna; Driessen, Marja; Benberin, Valery; Zhumadilov, Zhaxybay; Nurgozhin, Talgat; Urazova, Maira; et al. (BMJ, 2018)
ObjectiveChanges in the gut microbiota are increasingly recognised to be involved in many diseases. This ecosystem is known to be shaped by many factors, including climate, geography, host nutrition, lifestyle and medication. Thus, knowledge of varying populations with different habits is important for a better understanding of the microbiome.DesignWe therefore conducted a metagenomic analysis of intestinal microbiota from Kazakh donors, recruiting 84 subjects, including male and female healthy subjects and metabolic syndrome (MetS) patients aged 25–75 years, from the Kazakh administrative centre, Astana. We characterise and describe these microbiomes, the first deep-sequencing cohort from Central Asia, in comparison with a global dataset (832 individuals from five countries on three continents), and explore correlations between microbiota, clinical and laboratory parameters as well as with nutritional data from Food Frequency Questionnaires.ResultsWe observe that Kazakh microbiomes are relatively different from both European and East Asian counterparts, though similar to other Central Asian microbiomes, with the most striking difference being significantly more samples falling within thePrevotella-rich enterotype, potentially reflecting regional diet and lifestyle. We show that this enterotype designation remains stable within an individual over time in 82% of cases. We further observe gut microbiome features that distinguish MetS patients from controls (eg, significantly reduced Firmicutes to Bacteroidetes ratio,BifidobacteriaandSubdoligranulum, alongside increasedPrevotella), though these overlap little with previously published reports and thus may reflect idiosyncrasies of the present cohort.ConclusionTaken together, this exploratory study describes gut microbiome data from an understudied population, providing a starting point for further comparative work on biogeography and research on widespread diseases.Trial registration numberISRCTN37346212; Post-results.